Better by Design? Architecture, Urban Planning, and the Good City - https://doi.org/10.21061/better-by-design (Virginia Tech Publishing, 2020)
This book explores the intellectual roots of the design professions, showing how architects, planners, and other designers have traditionally interpreted their roles and implemented their ideas in cities across North America and the UK. Drawing on his long record of research and award-winning publications on the social production of the built environment, Paul Knox offers a critical appraisal of their ultimate effectiveness in achieving the goal of creating and sustaining good cities.